Investigation in to the Growing Problems of Alcoholism among Teenagers in Sierra Leone - Konneh, Khalifa; Koroma, Lahai (Research Developments in Arts and Social Studies Vol. 2, 2022)
This research work was geared towards investigatingthe growing problems of Alcoholism and binge drinking among teenagers in Kenema city, Sierra Leone. Questionnaires and interview schedules were carefully developed and administered to 400 people randomly selected from various part of Kenema City. The sample size comprised of Teenagers, Traders, Housewives, and Community leaders such as Imams, Pastors, Teachers, elders and Medical Laboratory Technicians. The structured questionnaire was divided into four sections each soliciting information on the Demographic characteristics or Personal information of the respondent, determination of the causes of growing problems of alcoholism and binge drinking, assessing and examining the health status/conditions of these teenagers and toexamine the awareness of the danger of alcoholism. The results of the research work indicated that 230 (57.5%) of the ages of 11 – 20 years of the youths were actively involved in alcoholism. With respect to the awareness alcoholism in the city 270 (67.5%) of respondents were aware of alcoholism the city and 130 (32.5%) had no knowledge of alcoholism. The Sawmill Section where alcohol was produced in the form of Bitter Root drink had the highest percentage (95%) within the Kenema city and with so many dwelling houses around the vicinity of the factory lot of health implications were envisaged by the inhabitants. The responses on the health status those who take alcohol indicated that, hydrated condition accounted for 10 respondents with a percentage of 2.5%, dehydrated condition accounted for 271 respondents with a percentage of 67.7%, Anaemic condition accounted for 60 respondents with a percentage of 15% and Insane condition accounted for 59 respondent with 14.7% of the respondents in the study area. This means that taking alcohol is dangerous to our health system let alone in excess as our young brothers are now doing, the required percentage for alcohol in the system according to WHO standard is 4.5%, above that figure there is going to be a health problem. It was also shown that those who take alcohol in the research area are marginalized by the community members.